Cytoskeletal-based mechanisms differently regulate in vivo and in vitro proplatelet formation - Alicia Bornert; Julie Boscher; Fabien Pertuy; Anita Eckly; David Stegner; Catherine Strassel; Christian Gachet; François Lanza; Catherine Léon (Haematologica, 2021)
Platelets are produced by bone marrow megakaryocytes through cytoplasmic protrusions, named native proplatelets (nPPT), into blood vessels. Proplatelets also refer to protrusions observed in megakaryocyte culture (cPPT) that are morphologically different. Contrary to cPPT, the mechanisms of nPPT formation are poorly understood. We show here in living mice that nPPT elongation is in equilibrium between protrusive and retraction forces mediated by myosin-IIA. We also found, using WT and β1-tubulin-deficient mice, that microtubule behavior differs between cPPT and nPPT, being absolutely required in vitro, while less critical in vivo. Remarkably, microtubule depolymerization in myosin-deficient mice did not affect nPPT elongation. We then calculated that blood Stokes'forces may be sufficient to promote nPPT extension, independently of myosin and microtubules. Together, we propose a new mechanism for nPPT extension that might explain contradictions between severely affected cPPT production and moderate platelet count defects in some patients and animal models.